PERAN WORLD WILDLIFE FUND DALAM MENCEGAH PENYELUNDUPAN SATWA LIAR DI INDONESIA - Dinda Ismaya; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine the role of the World Wildlife Fund in preventing the smuggling of wildlife in Indonesia and determine the obstacles experienced by the World Wildlife Fund in preventing the smuggling of wildlife in Indonesia. The author will focus on one issue, namely the role of WWF in preventing the smuggling of elephant ivory . World Wide Fund for Nature (WWF) is an international non-governmental organizations that deal with issues of conservation, research and restoration of the environment, formerly named the World Wildlife Fund and is still the official name in Canada and the United States. WWF is the largest independent conservation organization in the world with over 5 million supporters worldwide who work in more than 100 countries, supporting around 1,300. The method used in this paper is descriptive analytical method. This study shows that there are some roles carried out by WWF in preventing the smuggling of elephant ivory as a motivator, a communicator, an intermediary, organizational, legislative.Keywords: WWF, the smuggling of elephant ivory.